A 3.3-V ISDN U-interface line driver with a new IQ-control circuit. - Jinup Lim (IEEE Journal of solid state circuits)
In this work, we propose a new quiescent current (IQ) control circuit applicable to line drivers for digital subscriber line (DSL) applications. The line driver consists of preamplifier, error amplifiers, output transistors, and IQ control circuits. A new method is proposed for controlling IQ values in order to obtain high linearity performance. It also helps to determine the minimum off-current value of the class-AB output stage to reduce crossover distortion. The line driver is implemented for ISDN U-interface applications. It is fabricated in a 0.35-μm CMOS technology for a single power supply voltage of 3.3 V, and a total harmonic distortion of less than -64 dB is achieved.